Model pembelajaran student teams achievement divisions (STAD) untuk meningkatkan aktivitas dan hasil belajar PKn di kelas IV sekolah dasar - Untung Sudrajat (Jurnal Pendidikan Dasar, 2022)
This study aims to describe the improvement of Civics Learning Quality through the Student Teams Achievement Divisions (STAD) Learning Model for Fourth Grade Students of SD Negeri 1 Mlilir Semester 1 of the 2018/2019 Academic Year. This research was conducted at SD Negeri 1 Mlilir, Gubug District, Grobogan Regency. The type of action in this research is Classroom Action Research, namely Improving the Quality of Civics Learning through the Student Teams Achievement Divisions (STAD) Learning Model for Fourth Grade Students of SD Negeri 1 Mlilir Semester 1, from July to October 2018. The subjects of this school action research are students fourth grade at SD Negeri 1 Mlilir, Gubug District, Grobogan Regency with a total of 32 students. Repairs were held in 2 cycles. Each cycle consists of 4 stages, namely: the planning stage, the implementation stage, the observation stage, and the reflection stage. The results of school research can be said that the Quality of Civics Learning through the Student Teams Achievement Divisions (STAD) Learning Model in Grade IV Students of SD Negeri 1 Mlilir Semester 1 Gubug District, Grobogan Regency can increase, as evidenced by the results of the 34% pre-cycle completeness percentage data, increasing to 59% in cycle I. Then in cycle II the percentage of completeness again increased to 91%. In the first cycle of meeting 1 the data from the observations of students got an average score of 17.59 in the sufficient category and 28 in the sufficient category. In cycle II, student activity increased with the score at meeting 1 being 23.59 with a good category and meeting 2 being 27.53 with a good category.